Ulama & kekuasaan : pergumulan elite Muslim dalam sejarah Indonesia - Burhanuddin, Jajat, 1967- (Jagakarsa, Jakarta : MIZAN, 2012)
Role of Muslim elites in social life, political conditions, and history of Islam in Indonesia.
Translation of the author's thesis (doctoral)--Universiteit Leiden.
Includes bibliographical references (p. 423-465) and index.
Keywords: Muslims -- Indonesia -- History; Islam -- Indonesia -- History; Indonesia -- Politics and government; Indonesia -- Social life and customs